Kompetensi Literasi Digital Peserta Didik pada Mata Pelajaran Biologi - Hasliyah, Suci; Sofyan, Ahmad; Fadilah, Eva (CV. Creative Tugu Pena, 2022)
This research aims to obtain an overview of the digital literacy competency levels of students at each grade level in biology subjects based on four digital literacy competencies. The four competencies are Internet Searching, Hypertextual Navigation, Content Evaluation and Knowledge Assembly. This research uses a descriptive quantitative approach with a survey method. The sampling technique used was purposive sampling and the research sample was students at State Islamic Senior High School of 10 Jakarta. The instrument used is a questionnaire using a google form and an interview sheet. Quantitative data analysis technique is descriptive statistics. The results showed that the digital literacy competence of students in biology subjects obtained an average score of 64.93 which was in the sufficient category. Keywords: Competence Literacy, Digital Literation, Digital Competencey Literacy